Evaluating of altered hydration status on effectiveness of body composition analysis using bioelectric impedance analysis. Issue 1 (1st January 2020) - Ugras, Seda
ABSTRACT: Body composition analysis may provide valuable information about the assessment of balance between fluid, fat, and fat-free mass. The present study assessed whether the regular increase in water consumption has any significant effects on measurements of body composition using BIA. A total of 140 subjects participated in this study. Body composition analyses of the subjects were performed for five times using foot to foot BIA; first at baseline and four times, after 15 minutes of each 500 mL water intakes. There was overestimation in body fat mass compared to the baseline and increased significantly after water intakes in males (2.08% in 500 mL, 3.80% in 1000 mL, 5.88% in 1500 mL, and 7.92% in 2000 mL, p < 0.05) and in females (3.4% in 500 mL, 5.7% in 1000 mL, 7.8% in 1500 mL, and 9.4% in 2000 mL, p < 0.05). In contrast, there was markedly underestimation of total body water and fat-free mass in males (35% and 50%) and females (17% and 22%), respectively, at the end of the study. Thus, overestimation of body fat mass and lower estimation of total body water and fat-free mass with closely to the amount of water retention using BIA application should be considered in health-related clinical practice.